Prediction of Arterial Blood Gas from Venous Blood Gas: How Far We’ve Come - Siswanto, Putri Alief; Indriastuti, Endah (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2023)
Venous blood gas has been extensively studied as a replacement for arterial blood gas, which remains the gold standard despite some drawbacks. Many question the validity of venous blood gas for a routine clinical practice application. Arterial and venous pH are clinically interchangeable with a consistently narrow mean difference (bias: 0.03) and limits of agreement (LOA: -0.1 to 0.1). In contrast, arterial and venous pCO2 demonstrate a wide LOA (-20 to 20), while arterial and venous pO2 have a more pronounced difference. Many prediction studies showed a high correlation between arterial and venous pCO2 (r>0.7) yet a poor correlation between arterial and venous pO2 (r<0.3), suggesting a non-linear relationship. Leveraging the predictive power of artificial intelligence is paramount to modeling complex non-linear relationships between venous and arterial blood gas parameters, which may improve the estimation of arterial blood gas using venous samples.